Diversification of energy sources as a tool for strengthening EU energy security : Focus on LNG and the Czech Republic - Kapusta, Richard; Bič, Josef; Sejkora, Jiří, 1985-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the diversification of gas supply sources as a means of strengthening the energy security of the Czech Republic, with a specific focus on the role of liquefied natural gas (LNG). Following the disruption of Russian pipeline supplies and the shift in European energy priorities after 2022, LNG has become a crucial instrument for ensuring flexibility and reducing import dependence. The research analyses the Czech Republic’s preparedness for the long-term and sustainable utilization of LNG, focusing on access to import infrastructure abroad, the domestic transmission network, and storage capacity. It further assesses regulatory and contractual frameworks, risks, and potential development scenarios for LNG integration. The theoretical part of the thesis defines key concepts of energy security and diversification, while the practical part evaluates real infrastructure, available import routes, and strategic options for the Czech Republic. The aim is to provide a structured overview of the current state and future possibilities of LNG deployment as a component of national energy resilience.
Vedoucí práce: Josef Bič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses